(Em)placing recovery: Sites of health and wellness for individuals with serious mental illness in supported housing. (September 2017) - Piat, Myra; Seida, Kimberly; Sabetti, Judith; Padgett, Deborah
Abstract: This study used photo-elicitation methodology to explore how the move from supervised to supported housing affects recovery and community connections for individuals living with serious mental illness (SMI) in four Canadian cities. Qualitative interviews conducted in 2015 revealed five themes: (1) the characteristics distinguishing home from housing; (2) the importance of amenities offered by supported housing; (3) the connections between accessibility, mobility, and wellbeing; (4) the role of certain places in facilitating aspects of recovery such as offering hope or facilitating social connectedness; and (5) the concrete and metaphorical impact of changing vantage points on identity (re)construction. Utilizing therapeutic landscapes as an analytical framework, and combining insights from the health geography, and mental health (MH) housing and recovery literatures, this study deepens current understanding of how everyday places—conceptualized as therapeutic landscapes—directly and indirectly support MH recovery for individuals with SMI. Implications for research on housing, and on the spatial aspects of recovery processes are discussed. Highlights: Photo-elicitation is used to examine how supported housing facilitates recovery. 'Therapeutic landscapes' is a useful framework for mental health recovery. Place is a context for the physical and social processes of mental health recovery. Place-based analyses of recovery advance housing and health geography research.